PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTs. CERDAS MURNI TEMBUNG PADA POKOK BAHASAN ARITMATIKA SOSIAL TAHUN PELAJARAN 2014/2015 - Adriba Azni (Universitas Islam Negeri Sumatera Utara Medan, 2016)
This study aims to determine: 1) the results of students 'mathematicslearning on the subject of social arithmetic is taught with conventionallearning models in class VII MTs. Smart Pure Tembung., 2) the resultsof students' mathematics learning on the subject of social arithmetic istaught with learning models Cooperative Script in class VII MTs. SmartPure Tembung., 3) differences in the results of students' mathematicslearning on the subject of social arithmetic is taught with the learningmodel and conventional Cooperative Script in class VII MTs. SmartPure Tembung. The population in this study were students of class VIIMTs. Smart Pure Tembung consists of two classes totaling 72 people.Samples were two such classes, namely class VII-2 by learningCooperative Script as many as 35 students and class VII-1 byconventional learning as many as 37 students. Instruments thatresearchers use in this study is in the form of multiple-choice test of 10questions. Test material used is a matter of social arithmetic. Thefindings of this study were (1) the average value of students who usethe Cooperative Script is X ̅ = 79 with a standard deviation S = 12.78,(2) the average value of students who use conventional learning is X ̅ =58.65 with standard deviation S = 15.72, (3) testing the hypothesis byusing t test showed to> t table or 5.653> 1.994 with df = 70 at 5%significance level. This shows that there is a positive and significantinfluence learning outcomes math students taught by cooperativelearning model script.